PENERAPAN METODE KORESPONDENSI BERSAMA UNTUK ANALISIS PERUBAHAN PERILAKU PENGGUNA SMARTPHONE - Isowedha Widya Dewi; Mustafid Mustafid; Abdul Hoyyi (Jurnal Gaussian, 2014)
Competition is extremely tight in the technology sector including smartphones , the manufacturers compete to satisfy the desire of consumers with a variety of innovations. This study aims is form joint correspondence plot to determine whether consumers switch from one type to the other types of smartphones, as well as knowing what respondents consider when buying a smartphone . By adding a time variable data on methods of joint correspondence, changes in consumer behavior can be determined within a certain time . Time variables used was from 2011 to 2013 and smartphones that will be compared is Blackberry, Android and iOS. From the resulting graph can be seen that many kinds of smartphones used in each time variable and variables that affect the time of purchase . After doing research , showed that smartphone users in 2011, mostly used a Blackberry switched to Android in 2012 and 2013. Blackberry users at the time of puchase paid attention to the brand , color , design , and camera , but did not pay attention to prestige . Android users paid attention to completeness of the application , RAM , data capacity , color , resale price and network coverage . While iOS is not widely used by respondents from 2011 to 2013. iOS users considered the prestige , but did not consider the brand , design and battery life.